PENGARUH TRANSPORTASI JARAK PENDEK TERHADAP KADAR HORMON TIROKSIN (T4) DARAH KAMBING PERANAKAN ETTAWA - , MILUH MIRANINGTYAS ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Transportation is an important link in distribution of does from market to consumers. Those transportation commonly used can be short distance as well as long distance. If the transportation process was not done properly, the owner and the consumer will gain loss due to transportation stress. Physiological response that often overlooked is T4 hormone change. This hormone can be used as indicator of metabolism change. This study aimed to determine the effect of short distance transportation toward the level of T4 hormone. This study using five Peranakan Ettawa (PE) does. All of does were transported in distance of 35 km in an hour with vehicle speed 35 km/h. Blood sampling done three times, before transportation, after transportation and seven days after transportation. Blood was taken from jugular vein collected in ependorf tube, and then centrifuged 3000 rpm in five minutes. This followed with enzym-linked immunosorbent assay (ELISA) test to determine the T4 hormone level in does serum. This study result T4 hormone level before transportation is 22.06743±7.03 μg/ml, after transportation is 14.37968±2.91 μg/ml and seven days after transportation is 19.65508±5.82 μg/ml. Data analysis using Analysis of variance (ANOVA) oneway, the result shows that short distance transportation did not significantly affect the T4 hormone changes (P> 0.05). It can be concluded the short distance transportation was not effected in the concentration T4 hormone of crossbreed does.